Amphibole-bearing metamorphic clasts in ANDRILL AND-2A core: A provenance tool to unravel the Miocene Glacial history in the Ross Embayment (western Ross Sea, Antarctica) - TALARICO, F. M.; Pace, D.; Sandroni, S. (Geosphere, 2011)
A petrological investigation of amphibolebearing metamorphic clasts in the ANDRILL AND-2A core allows a detailed comparison with similar lithologies from potential source regions, leading to the identifi cation of three distinct provenance areas in the present-day segment of the Transantarctic Mountains between the Byrd Glacier and the Blue Glacier (Mulock-Skelton glacier area, the Britannia Range, and the Koettlitz-Blue glacier area in the Royal Society Range). A key role in the comparison is played by the wide range of Ca-amphibole compositions, type of intracrystalline zoning, mineral assemblages, and fabrics, which refl ect different bulk rocks and metamorphic conditions. Ca-amphibole compositions and zonations also offer the opportunity for the application of geothermobarometry methods, which, consistent with literature data, provide further evidence that the three provenance regions correspond to distinct metamorphic terrains with pervasive medium-pressure amphibolitegrade conditions restricted to the Britannia Range. The study contributes new insights into the depositional processes in a variety of glacial environments ranging from open marine with icebergs to distal, proximal, and subglacial settings. The results also highlight the record of two distinct glacial scenarios refl ecting either short-range (<100 km) fl uctuations of paleoglaciers in the Royal Society Range with dominant fl ows from W to E, or larger volume of ice sourced from southernmore outlet glaciers from the Skelton-Byrd glacier area with fl ow lines running N-S close to the Transantarctic Mountains front. Both scenarios demonstrate the importance of the AND-2A core to reveal a hitherto unavailable, near-fi eld record of dynamic paleoenvironmental history through the Miocene. © 2011 Geological Society of America.